2005
DOI: 10.1007/s10540-005-2897-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Effect on Respiration of Heart Mitochondria: Influence of Various Factors

Abstract: The effect of exogenous cytochrome c on respiration rate of the rat and human heart mitochondria was assessed in situ, using permeabilized fibers. It was (i) much more pronounced in State 2 and 4 than in State 3 with all the respiratory substrates (pyruvate+malate, succinate, palmitoyl-CoA+carnitine and octanoyl-L-carnitine), (ii) different with different substrates, (iii) much higher after ischemia in both metabolic states, particularly in the case of succinate oxidation compared to pyruvate+malate, (iv) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…42 In this study (Fig. 4B), the increase of respiration rate in state 2 with pyruvate + malate due to ischemia-reperfusion was not observed when compared with the control data presented in Figure 4A and the usually obtainable control respiration rates of isolated mitochondria.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…42 In this study (Fig. 4B), the increase of respiration rate in state 2 with pyruvate + malate due to ischemia-reperfusion was not observed when compared with the control data presented in Figure 4A and the usually obtainable control respiration rates of isolated mitochondria.…”
Section: Discussioncontrasting
confidence: 50%
“…43 The high degree (2-fold) of stimulation of respiration by cytochrome c in state 3 in mitochondria isolated from ischemia-reperfusion-treated hearts indicates the damage of the outer membrane of the mitochondria and the possible cytochrome c release from the mitochondria, which often causes state 3 respiration rate decrease. 42,44 However, GBE treatment (neither concentration, 0.05 and 0.4 mL) of rat hearts did not affect the cytochrome c test value, suggesting that GBE did not prevent the damage of outer mitochondrial membrane and cytochrome c loss from mitochondria during the ischemia-reperfusion period (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…It was found that quercetin at higher concentration (30-50 μM) and in some conditions can do it (Ortega and García 2009) and cause the decrease in mitochondrial respiration rate. To check this possibility we applied cytochrome c test (Toleikis et al 2005). We observed large enhancement of depressed by EGb761 mitochondrial respiration both in the absence and presence of ADP after addition of pure cytochrome c into incubation medium (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration is ceased when the substrate and ADP are absent (State I), 20 and slightly activated when only the substrate succinate is present (State IV). 5 This translated to the comparable deformation of isolated mitochondria.…”
Section: Discussionmentioning
confidence: 99%